To a painfulheart, chaotic ions: Relationship between diseases of the cardiac conduction system and ionic concentration alterations. - Parra-Pérez, Anna Sofía (2022)
Background: The human cardiac conduction system allows the propagation of the electrical signal from the heart through the entry and exit of ions that depolarize the cardiac cells to generate an action potential. Although ions such as calcium, potassium, phosphorus, chlorine and sodium regulate cardiac physiology, abnormal alterations in their concentration are associated with different heart diseases. Aim: Describe the relationship between heart disease and possible alterations of the sinus conduction system with respect to alterations in ionic concentrations. Materials and methods: A systematic search of the literature is carried out in PubMed, according to the PRISMA Declaration, through the combination of the health descriptors "Cardiac conduction system diseases" and "electrolytes" using the Boolean AND connector. Results: 92 articles were analyzed according to the following discussion categories: eight belonged to the population category, 15 were included in drugs, substances and therapies, 49 related electrolyte changes to possible clinical conditions, and 28 articles dealt with diseases possibly related to electrolyte imbalances. Conclusion: A relationship can be found between diseases, medications and their effects, and post-operative management, which can lead to an electrolyte imbalance. Most of the factors that cause heart disease are related to alterations in electrolyte imbalance. Much of these alterations can be corrected. Establishing changes in lifestyle, diet and drug therapy may help improve these alterations.